Character Construction in The Excranization of Danur: From Risa’s Perspective in The Novel to The Film’s Visual Interpretation - Juliana; Afriana (IKIP Siliwangi, 2025)
The building of the primary character, Risa, during the excranization process from Risa Saraswati's novel Danur to its Awi Suryadi-directed film adaptation is examined in this study. The study focuses on the novel's use of first-person narrative to depict Risa's character and how the movie uses visual and cinematic aspects to do the same. This study examines the narrative strategies, character growth, and emotional depth that are communicated through textual versus visual storytelling using a comparative analysis method. The theoretical framework, which focuses on character representation and the change in perspective from internal (literary) to outward (cinematic), is founded on adaption theory and narratology. The results show both losses and improvements in the adaption process, revealing notable shifts in the way Risa's inner thoughts, emotional challenges, and supernatural encounters are conveyed. Character adaption in horror genres, especially in Indonesian literature and film, is better understood thanks to this research.